Modifying crystallinity, and thermo-optical characteristics of Paulownia biomass through ultrafine grinding and evaluation of biohydrogen production potential. (1st October 2020) - Yi, Wang; Nadeem, Faiqa; Xu, Guangyin; Zhang, Quanguo; Joshee, Nirmal; Tahir, Nadeem
Abstract: Exploring the clean and low cost biohydrogen production technology with vastly spread forestry based biomass highlights the practical large scale biohydrogen production prospective. In the present work we exploited the role of ultrafine pretreatment to Paulownia biomass as a sole carbon source to evaluate biohydrogen production potential. The altered physical, thermal and optical characteristics of Paulownia biomass after pretreatment of ultrafine grinding were compared with well-studied biomass of corn stover. Microstructural, FTIR and TGA analysis highlight the deterioration of crystal structure and lignin breaking of cellulose with increase in pretreatment time, which significantly improves hydrolysis and enhances hydrogen production subsequently. In comparison to raw materials, Paulownia leaves have the highest hydrogen production potential whereas after pretreatment, total hydrogen yield from Paulownia stems is increased by 51.8% which is comparable to corn stover. Our results highlight that in comparison to conventional agriculture stover, lignocellulosic Paulownia biomass can be potential candidate for clean energy production with prospective of sustainable supply. Graphical abstract: Image 1 Highlights: SEM confirms reduction of particulates and deterioration of surface. XRD reveal disordering of crystal structure of cellulose after ultrafine grinding. TGA measurements suggests remarkable breaking of lignin after grinding of 8 h. Crystallinity band around 1375 cm −1 is considerably modified at 8 hrs of grinding. Pretreatment increases total hydrogen yield of PS(51.75%), as compare to CS(20.59%).